Modeling Method and Inherent Characteristic Analysis of Cycloid Pin Gear Transmission - Xueping Song; Aibin Bi; Bowen Lu (Jixie chuandong)
The cycloid pin wheel drive system is taken as the research object， and the nonlinear dynamics model of bending torsion coupling is established by using the method of concentrated mass. Considering the eccentric motion of cycloid and the influence of time-varying stiffness， backlash and transmission error of cycloid and pin gear， the differential equation of motion of the system is obtained by Lagrange method. According to the characteristics of positive semidefinite， variable parameters and strong nonlinearity of the system differential equation， the relative meshing displacement of the cycloid wheel and the pin wheel is taken as the generalized coordinate of the system. By using linear transformation， the equations are transformed into a unified matrix form， and the equations are dimensionless. The natural frequency and dimensionless frequency of the system are obtained by calculation， and the influencing factors of the natural frequency are analyzed.